Rotating Hydromagnetic Two-Fluid Convective Flow and Temperature Distribution in an Inclined Channel - Sri Ramachandra Murty, P.; Balaji Prakash, G.; Karuna Sree, Ch. (International Journal of Engineering and Technology, 2018)
Magnetohydrodynamic convective two-fluid flow and temperature distribution between two inclined parallel plates in which one fluid being electrically non-conducting and the other fluid is electrically conducting is studied. A constant magnetic field is applied normal to the flow. The system is rotated about y-axis with an angular velocity ‘W’.  Perturbation method is used to obtain solutions for primary velocity, secondary velocity and temperature distribution by assuming that the fluids in the two regions are incompressible, laminar, steady  and  fully  developed.  Increasing  values  of  rotation  is  to  reduce  temperature  distribution  and  primary  velocity where as thesecondary velocity increases for smaller rotation, while for larger rotation it decreases.